The properties of geopolymer concrete incorporating red sand as fine aggregate - Soltaninaveh, Kaveh (Curtin University, 2008)
Concrete is the most common building material in the world and its use has been increasing during the last century as the need for construction projects has escalated. Traditionally, concrete uses Ordinary Portland Cement (OPC) as binder, water as the activator of cement and aggregate. Finding an appropriate replacement for traditional concrete is a desirable solution to obviate the environmental problems caused by cement production. The use of fly ash as a partial replacement for Portland cement is a method to maintain the properties of concrete and reduce the need for cement. Fly ash is a by-product from coal-fired power plants and is abundantly available. The percentage of cement replacement can be varied according to application and mix design. One of the potential materials to substitute for conventional concrete is geopolymer concrete (introduced by Davidovits in 1979). Geopolymer concrete is an inorganic alumino-silicate polymer synthesized from predominantly silicon, aluminum and byproduct materials such as fly ash. Geopolymer properties have been investigated for several years and it is still a major area of interest among researchers and industry partners as it does not contain cement and uses fly ash and alkali liquids as binders to produce a paste to consolidate aggregates. Furthermore, the aggregate comprises a substantial portion of concrete. Including coarse and fine aggregates it is normally obtained from natural sources. Fine aggregate in Australia is usually mined from sand quarries. As the demand for concrete production increases, more natural sand is needed. The need for fine aggregate should be addressed in an environmentally friendly manner, considering the diminishing sources of natural sand. Red sand is a by-product generated from the manufacture of alumina from bauxite by the Bayer process.Previous studies on properties of red sand have shown that it has the potential to be used in concrete as a fine aggregate. While the use of red sand in traditional concrete has been investigated by some researchers, no research has been reported regarding the use of this by-product in manufacturing geopolymer concrete. This research looks into the replacement of natural sand fine aggregates with red sand in geopolymer concrete. Initially, an extensive series of mixtures was prepared and tested. The objective of the research was to identify the salient parameters affecting the properties of geopolymer concrete when natural sand is replaced by red sand. At the next stage, attempts were made to enhance the mechanical and durability features of red sand geopolymer concrete. The final stage consisted of testing red sand geopolymer concrete to find out the various properties of this novel construction material.